2016
DOI: 10.17707/agricultforest.62.4.05
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Non-Genetic Factors on Daily Milk Production in Awassi Breed of Sheep in Macedonia

Abstract: SUMMARYSeveral basic -fixed factors on daily milk yield have been examined in total of 132 Awassi breed sheep, during two -year production period (2011 and 2012). The examination includes the following factors: lactation number, lactation type, date of milk recording, number of newborn lambs, month or year of milk recording and length of suckling period. Their influence on individual milk yield measured in morning, afternoon and evening milking, total daily milk yield and percentage of milk fat has been exami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 1 publication
1
6
0
Order By: Relevance
“…The second one is that the typemodel for genetic evaluations, which is based on milk yield of separate milking during the test day, has not yet been discussed in literature. Pacinovski et al (2014) determined significant influence of month of milk test on above mentioned traits (morning, afternoon and evening milk) in Awassi sheep and similar results obtained Alkass et al, (2008) in Awassi sheep in Iraq. More detailed studies and gathering more information will be necessary in future to compare with the model of daily milk yield, as correlations and genetic relations between individual measurements of milk production during the test day.…”
Section: Influence Of Month Of Milk Testsupporting
confidence: 83%
See 3 more Smart Citations
“…The second one is that the typemodel for genetic evaluations, which is based on milk yield of separate milking during the test day, has not yet been discussed in literature. Pacinovski et al (2014) determined significant influence of month of milk test on above mentioned traits (morning, afternoon and evening milk) in Awassi sheep and similar results obtained Alkass et al, (2008) in Awassi sheep in Iraq. More detailed studies and gathering more information will be necessary in future to compare with the model of daily milk yield, as correlations and genetic relations between individual measurements of milk production during the test day.…”
Section: Influence Of Month Of Milk Testsupporting
confidence: 83%
“…The limited number of sheep in flock would require inclusion of as many heads and similar data for all lactations, in order to achieve higher accuracy in the process of evaluation. Pacinovski et al (2014) also found significant influence of lactation on above mentioned traits (morning, afternoon and evening milk) in Awassi breed of sheep.…”
Section: Influence Of Number Of Lactationmentioning
confidence: 56%
See 2 more Smart Citations
“…5). A highly significant influence of this factor on daily milk production was also determined in another survey in Awassi sheep (Pacinovski et al, 2014).…”
Section: Resultsmentioning
confidence: 68%